Rickettsia parkeri hijacks tick hemocytes to manipulate cellular and humoral transcriptional responses - Adegoke, Abdulsalam; Ribeiro, Jose M. C.; Brown, Sidney; Smith, Ryan C.; Karim, Shahid (Frontiers in Immunology, 2023)
Blood-feeding arthropods rely on robust cellular and humoral immunity to control pathogen invasion and replication. Tick hemocytes produce factors that can facilitate or suppress microbial infection and pathogenesis. Despite the importance of hemocytes in regulating microbial infection, understanding of their basic biology and molecular mechanisms remains limited. Here we combined histomorphology and functional analysis to identify five distinct phagocytic and non-phagocytic hemocyte populations circulating within the Gulf Coast tick Amblyomma maculatum. Depletion of phagocytic hemocytes using clodronate liposomes revealed their function in eliminating bacterial infection. We provide the first direct evidence that an intracellular tick-borne pathogen, Rickettsia parkeri, infects phagocytic hemocytes in Am. maculatum to modify tick cellular immune responses. A big RNA-seq dataset generated from hemocytes isolated from uninfected and R. parkeri-infected partially blood-fed ticks generated ~40,000 differentially regulated transcripts, >11,000 of which were immune genes. Silencing two differentially regulated phagocytic immune marker genes (nimrod B2 and eater-two Drosophila homologs), significantly reduced hemocyte phagocytosis. Together, these findings represent a significant step forward in understanding how hemocytes regulate microbial homeostasis and vector competence.